Literature Review : Kandungan Fitokimia dan Potensi Daun Teh Hijau (Camellia sinensis) dalam Menurunkan Risiko Obesitas - Priyanka Lestari (STIKES Columbia Asia Medan, 2025)
Green tea (Camellia sinensis) belongs to the genus Camellia from the Theaceae family. This plant has been used as traditional medicine for generations and is known to have various pharmacological activities. The purpose of this review is to discuss the benefits of green tea in reducing the risk of obesity by reviewing its botanical characteristics, phytochemical content, use and bioactivity to treat obesity obtained and compiled from literature searches through search engines such as Google Scholar, Science Direct, and PubMed. then discussed narratively. The results obtained indicate that green tea extracts and drinks can reportedly help increase the body's metabolism, which contributes to the reduction of body fat. Many studies report that this plant contains phytochemical compounds such as flavonoids, alkaloids, steroids, triterpenoids and carbohydrates. Epigallocationchin-3-gallate, L-theanine, and caffeine, which are respectively classified as flavonoids, amino acids, and alkaloids, are considered responsible for their pharmacological activity in treating obesity. EGCG has a hypocholesterolemic effect and suppresses cholesterol absorption in the intestine, L-theanine itself has physiological effects such as relaxation activities, and caffeine is useful in reducing food intake and has a thermogenic effect which can encourage weight loss.